OC-018 Obesity and type 2 diabetes are predominant risk factors underlying previously undetected cirrhosis in the general population. (22nd June 2015) - Harman, DJ; Wilkes, EA; James, MW; Ryder, SD; Card, TR; Aithal, GP; Guha, IN
Abstract : Introduction: Epidemiological studies have attributed the rising cirrhosis incidence and mortality in the UK predominantly to excess alcohol consumption. However, obesity acts synergistically with alcohol to increase the risk of cirrhosis. In addition, asymptomatic liver disease goes undetected; as a result nearly 50% of cirrhotics are diagnosed when presenting with hepatic decompensation. We utilised Transient Elastography (TE) to screen at-risk individuals in the general population, aiming to establish the prevalence of undetected liver cirrhosis and the risk factors underlying these cases. Method: The study was undertaken in 4 general practices in Nottingham between February 2012 and September 2014. The total adult patient population was 20, 868. Patients with pre-defined risk factors for chronic liver disease (hazardous alcohol use as identified by general practitioner (GP), type 2 diabetes and/or persistent ALT rise with negative serology) were identified from the GP electronic records and invited for TE even if liver enzymes were normal. TE was performed by trained nurses at the general practice sites. Liver stiffness of ≥8 kilopascals prompted review by a Consultant Hepatologist and liver cirrhosis was confirmed by established histological, radiological and biochemical methods. Results: Of 2, 022 patients eligible, 919 attended TE; 899 (97.8%) had valid liver stiffness measurements. Elevated liver stiffness was detected in 230 patients (25.6%) and cirrhosis in 26 (2.9%). Liver enzymes were normal in 16/26 (61.5%) of cirrhosis cases. Prior to the study, 23 patients with cirrhosis (aetiologies: alcohol (14), viral hepatitis (5), Non-alcoholic steatohepatitis (1), other (3)) had been identified; a diagnosed cirrhosis prevalence which was not significantly different compared to general population estimates of 76.3 cases per 100, 000. Following the study, the prevalence of cirrhosis diagnosis was 49/20, 868 (234.8 cases per 100, 000 (95% CI 201.3–268.3)) was 3 fold higher than the previous general population estimate. Risk factors for new cirrhosis diagnoses were obesity and/or type 2 diabetes in 16 patients (61.5%), alcohol alone in 3 (11.5%) and both alcohol and obesity and/or diabetes in 7 (26.9%). Conclusion: Investigating defined risk factors for liver disease using TE in a community setting detects a significant amount of previously unidentified cirrhosis. Cirrhosis prevalence in the general population is at least 3 times recent UK estimates. Obesity and type 2 diabetes are the predominant risk factors underlying previously undetected cirrhosis cases. Disclosure of interest: None Declared.